Collaborative Governance dalam Pelaksanaan Edutourism di Ubud (Studi Kasus Ubud Writers & Readers Festival) - Marmika, Putu Trisna; Supriliyani, Ni Wayan; Yasintha, Putu Nomy (CITIZEN CHARTER, 2020)
ABSTRACT Ubud Writer & Readers Festival is one of the tourism event that promotes edutourism in order to increase the number of tourist to visit Ubud. Through a collaborative governance system, the expected of the implementation can have an impact to all stakeholders in Ubud. Over all the collaboration faced problems, especially in communication between stakeholders and trust among them is still minimal. The research method used in this research was descriptive qualitative. The analysis uses the Collaboration Process indicator by Ansell & Gash and the Collaboration Measure of Success by Deseve. The result shows that the dominance of the foundation is so large that it makes the role of stakeholders in it is invisible. The Ubud Writers & Readers Festival is expected to be run through a collaborative system, but the fact shows that the implementation is carried out self handedly by the foundation. Keywords: Collaborative governance, Edutourism, Ubud Writers & Readers Festival.